Review on Parad Dosha and its Shodhana - Vani, Gayathri P A; Goyal, Manisha; Shukla, Govind Shay; Agarwal, Rajaram (International Research Journal of Ayurveda & Yoga, 2022)
Rasa shastra has given an auspicious position to Parada as it has been considered as the physical essence of Lord Shiva. Vedas also consider Parada as a gift of nature. The classical test Rasaratna Samucchaya states that “Siddhae rase Karishyami Nirdraaridrayam agadam jagat” exposes the magical effect of Parada. Even though, administration of Asudha Parada causes severe illness than that of poison. As it is associated with a lot of impurities, it is advised to do both Samanya Shodhana, and Visesha Shodhana (general and specific purificatory methods before its internal administration. Otherwise these impurities may cause various toxic effects in body ranging from mild fever to death. Hence Rasa acharyas mentioned a number of purificatory procedures both general and specific to eliminate the doshas associated with Parada. As per modern science Mercury comes in three forms (Elemental, inorganic and organic), each with its own set of symptoms. The brain is the primary target organ for breathed mercury vapor, whereas mercurous and mercuric salts harm the gut lining and kidneys, confirming persistent exposure and methyl mercury are widely disseminated throughout the body. This article focuses on various doshas associated with Parada and its purificatory procedures. P